ULTRASOUND DIAGNOSTICS OF HIP JOINT DYSPLASIA IN CHILDREN: A COMPARATIVE ANALYSIS WITH X-RAY IMAGING (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Hip joint dysplasia (HJD) is a significant concern in pediatric orthopedics, particularly in neonates. Early detection and appropriate management are essential to prevent long-term complications such as gait abnormalities or osteoarthritis. This study evaluates the effectiveness of ultrasound (US) as a diagnostic tool for HJD in comparison to conventional X-ray imaging. Data from 60 pediatric cases were analyzed to compare the sensitivity, specificity, and overall accuracy of these modalities. The study concludes that ultrasound is superior in early detection and offers a safer, non-invasive alternative to X-ray, particularly in infants under six months.